New skulls of Kolpochoerus phacochoeroides (Suidae, Mammalia) from the late Pliocene of Ahl al Oughlam, Morocco - (:unkn) unknown (My University, 2004)
The discovery of two male skulls of Kolpochoeroides phacochoeroides in the late Pliocene of Ahl al Oughlam in Morocco, and the revision of the whole collection from this locality, allows to complete the description of this North-African form, to estimate its sexual dimorphism and the extent of individual variation in a large isochronous sample, to reveal some ontogenic changes, and to confirm its distinction as a species of its own, as its cranial proportions (large occipital, short snout) and tooth characters (reduced incisors and premolars, complicated third molars) set it clearly aside from the East and South African forms. A cladistic analysis shows that K. phacochoeroides and Hylochoerus are the terminal branches of the Kolpochoerus clade, which is the sister-group of Potamochoerus.
Keywords: African Research